Доведення до самогубства шляхом використання Інтернет технологій як об’єкт криміналістичного дослідження - Маланчук, А.; Malanchuk, A. (Юридичний вісник. - 2022. - № 5. - С. 281-289, 2022)
З’ясовано, що криміналістичне дослідження доведення до самогубства шляхом використання Інтернет технологій полягає у визначенні специфіки механізму їх учинення та формування з її урахуванням відповідної окремої криміналістичної методики. Встановлено, що ознаки самогубства безпосередньо впливають на способи вчинення доведення до нього та слідову картину, зокрема психологічні властивості особи потерпілого використовуються як критерій обрання їх в якості жертви та для здійснення впливу на них, у тому числі з використанням Інтернет технологій, для схиляння їх до самогубства.

In this article, it has been emphasized that recently the use of cyberspace to influence individuals or a group of individuals in order to drive them to suicide has become quite widespread. It has been emphasized that there are currently no forensic studies of the phenomenon of suicide in the context of committing suicide by using Internet technologies. It has been found that the forensic investigation of suicide by using Internet technologies consists in determining the specifics of the mechanism of their commission and forming, taking into account it, a corresponding separate forensic methodology. It has been established that the signs of suicide directly affect the methods of committing suicide and the subsequent picture, in particular, the psychological properties of the victim are used as a criterion for choosing them as a victim and for influencing them, including using Internet technologies, to incline them to suicide. It has been noted that the criminal chooses Internet technologies to commit suicide, because they allow faster and more efficient selection of victims and their processing; to disguise one’s identity and traces of a criminal offence. A forensic definition of suicide by using Internet technologies has been proposed as a system of criminally punishable socially dangerous acts committed with the help of information and telecommunication systems and networks in order to induce a person to commit suicide. The main reason for the use of Internet technologies in the mechanism leading to suicide is the information-virtual addiction (cyber addiction) of the victims, which is formed under the influence of the “climate” in the family and team at the place of work and/or study. Signs of suicide directly affect the methods of committing suicide and the resulting picture, in particular, the psychological properties of the victim are used as a criterion for choosing them as a victim and for influencing them, including using Internet technologies, to incline them to suicide. In particular, the criminal chooses Internet technologies to commit suicide, because they allow faster and more efficient selection of victims and their processing; to disguise one’s identity and traces of a criminal offence.

Выяснено, что криминалистическое исследование доведения до самоубийства путем использования Интернет технологий заключается в определении специфики механизма их совершения и формирования с учетом соответствующей отдельной криминалистической методики. Установлено, что признаки самоубийства оказывают непосредственное влияние на способы совершения доведения до него и следовую картину, в частности психологические свойства личности потерпевшего используются как критерий избрания их в качестве жертвы и для воздействия на них, в том числе с использованием Интернет технологий, для склонения их к самоубийству. .
Committing suicide through the use of Internet technologies as an object of forensic research
Маланчук, А. Доведення до самогубства шляхом використання Інтернет технологій як об’єкт криміналістичного дослідження / А. Маланчук // Юридичний вісник. - 2022. - № 5. - С. 281-289. - DOI: https://doi.org/10.32782/yuv.v5.2022.32.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; доведення до самогубства; bringing to suicide; доведение до самоубийства; Інтернет-технології; Internet technologies; Интернет-технологии; кримінальне правопорушення; criminal offence; уголовное правонарушение; механізм учинення кримінального правопорушення; mechanism of committing a criminal offense; механизм совершения уголовного преступления; криміналістична методика; forensic technique; криминалистическая методика; суїцид; suicide; суицид; Кримінологія. Criminology. Криминология